Children's Acquisition of Morphosyntactic Variation. Issue 2 (3rd April 2022) - Shin, Naomi; Miller, Karen
ABSTRACT: This article presents a developmental pathway for the acquisition of morphosyntactic variation. Although there is abundant evidence that morphosyntactic variation is pervasive among adults, much less is known about how children acquire such variation. The literature thus far indicates that the pathway of development involves first producing only one of the variable forms (Step 1), producing both forms but in mutually-exclusive contexts (Step 2), then producing both forms in some overlapping linguistic contexts (Step 3), and finally producing both forms in more contexts (Step 4). The research reviewed indicates that input patterns are influential each step of the way, playing an important role in determining children's use of forms as well as the contexts in which the forms are produced. In addition to considering input effects, we also draw on various tendencies that children evince in the face of variable input to explain the pathway of development, including regularization and assigning different meanings to different forms. The article also includes suggestions for testing the hypotheses generated by the proposed pathway of development, which we illustrate by drawing on the acquisition of variable Spanish subject pronoun expression.